2003
DOI: 10.1245/aso.2003.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Locally Recurrent Colorectal Cancer in the Presence of Distant Metastases: Can It Be Justified?

Abstract: The presence of M1 disease per se should not preclude resection of local recurrence, although case selection is problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 19 publications
2
15
0
4
Order By: Relevance
“…Similar observations were made in local recurrences of colorectal cancer. The authors suggested that absence of gross residual tumor after resection was an independent prognostic factor [15,16]. Of note, the extent of disease correlated significantly with both the overall and progression free survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were made in local recurrences of colorectal cancer. The authors suggested that absence of gross residual tumor after resection was an independent prognostic factor [15,16]. Of note, the extent of disease correlated significantly with both the overall and progression free survival.…”
Section: Discussionmentioning
confidence: 99%
“…The median overall survival time according to the extent of the disease was 18 months (95% CI, [17][18][19] for the disease limited to the ovaries, 17 months (95% CI, 2-32) for the disease confined to the pelvis, and 9 months (95% CI, [3][4][5][6][7][8][9][10][11][12][13][14][15] for the disease beyond the pelvic cavity (P ¼ 0.0005) (Fig. 2).…”
Section: Surgical Treatment and Outcomementioning
confidence: 99%
“…bietet sich die Umstellung der Therapie auf FOLFIRI an [539]. Nach 5-FU-Monotherapie sind Therapiemöglichkeiten die Irinotecan-Monotherapie [117,465] gestellt werden [226]. Zur lokalen Tumorbehandlung besteht die Möglichkeit einer Stentversorgung [38,44,330,529,544,568] oder Durchführung einer Laser-bzw.…”
Section: Empfehlungunclassified
“…Provided distant deposits are resectable, highly selected patients can still experience good outcomes and survival beyond 5 years is possible. [32][33][34][35][36][37][38] Where outcome data were not described, or inseparably grouped together for patients with different pathologies (eg, recurrent rectal and cervical) or different treatments (eg, radiotherapy alone or combined with surgery), the fields are left blank. Where results have been provided for both curative and palliative procedures, the overall results for patients undergoing surgery are presented.…”
Section: Diagnosis and Evaluation Of The Patientmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] It is the authors' preference to treat the local recurrence ahead of metastatectomy. Relative and absolute contraindications to resection are listed in Table 3 (including examples in Figs.…”
Section: Anatomical Region Definitionmentioning
confidence: 99%